The Effectiveness of life skills training on support and acceptance of teachers - Karizaki, Atefeh Nazeri; Sidan, Seyyed Abolghasem (Opción, 2019)
This study was conducted to assess the effectiveness of life skills training on social support and social acceptance of female teachers. Data were analyzed using covariance analysis. As a result, the level of perceived support by friends (P 0.05 and f (1.25) = 418/33) and social acceptance feeling (P 0.05 and f (1, 25) =344 / 68) has a positive impact on female teachers. In conclusion, teaching self-awareness, empathy, effective communication and interpersonal relationships to female teachers has increased the overall perception of support and the level of perception of support by family and friends.